IMPLEMENTASI PENGEMBANGAN KARIR APARATUR BADAN PENGELOLAAN KEUANGAN & ASET DAERAH KABUPATEN PUNCAK JAYA - Wonda, Alexander Ronaldo; Ohoiwutun, Yoshepina; Sapioper, Hiskia C.M. (Universitas Cenderawasih, 2023)
This study aims to examine and analyze the Implementation of Civil Servant Career Development Policies at the Regional Financial and Asset Management Agency of Puncak Jaya Regency, as well as analyze the factors that support and hinder the implementation of these policies. This type of research is a descriptive research with a qualitative approach, data collection techniques using observation, interviews, and documentation. Data analysis consisted of three stages, namely data reduction, data presentation, and drawing conclusions. The results of this study can be concluded that the Implementation of Civil Servant Career Development Policy at the Regional Financial and Asset Management Agency of Puncak Jaya Regency by using Edward III's theory in the aspect of communication regarding employee education is already good. from the aspect of resources in the implementation of training or training constrained by budget problems. In the disposition aspect for career development there are still doubts about activities such as seminars, workshops. Then from the aspect of bureaucratic structure in the implementation of basic education training, many of them were not carried out optimally. Supporting and inhibiting factors for the Implementation of Civil Servant Career Development Policy at the Regional Financial and Asset Management Agency of Puncak Jaya Regency are among the apparatus at the Regional Financial and Asset Management Agency, causing uncertainty and doubt in determining the career path of these apparatus